Land and natural resources: central issues in the peace and democratisation process in Nepal - Khadka, Keshab (Economic Journal of Development Issues, 2012)
Land has been the central issue to human society since the dawn of civilization. Primitive society took it as free gift of nature. Land and livelihood has become the intertwined focal issues in the epochal social transformation processes famous in different era of human civilizations which gave birth to the problem of ownership entitlement, the milestone of turning land as source of state power. Actually, review and reappraisal of land relations has remained always a hot issue in all revolutionary changes and Nepal could not be an exception to this trend. Nepal needs, in fact, a package programme of infrastructure facilitations widening rural access along with strengthening farm input hardware such as full season irrigation, all weather transportation network, cheaper electrification, mechanization with technical supports, cooperatives extending in both output increment and marketing promotions for landless and marginal farmers based on participatory approach. The environment friendly management of water and forest resources to boost up bio-diversity based farming technology is urgently feltneed for which they fought lifelong and supported the peoples’ movement. Key words: Land and natural resources; Peace and democratisation process; Package programme; Nepal Economic Journal of Development Issues Vol. 11 & 12 No. 1-2 (2010) Combined Issue Page:47-68 Uploaded date: 10 April, 2012